The Construction of Instructional Package on Critical Thinking and Figure of Speech Skills by Using Thai Popular Songs for Matthayomsuksa 3 Students of Ban Mae Kham School (Prachanukhor), Mae Chan District, Chiang Rai Province - เสี่ยงกุศล, วิไลพร; จันทร์เรือง, ยุพิน; อุทยานุกูล, ปฏิพันธ์ (Ganesha Journal, 2019)
The aims of this study were to 1) construct and examine the efficiency of the instructional package on critical thinking and figure of speech skills by using Thai popular songs, 2) investigate the students’ achievement before and after implementing the instructional package, and 3) assess the student’s satisfaction towards the use of instructional package. The population was 83 Matthayomsuksa 3 students of Ban Mae Kham School (Prachanukhor) from 3 classes in the semester 1/2019. The samples were 27 students from class 3/1 selected by cluster random sampling using class as selecting factor. The research instruments were 8 sets of the instructional package on critical thinking and figure of speech skills by using Thai popular songs, 8 learning management plans, 40-item achievement test, and 20-item students’ satisfaction questionnaire. The researcher conducted pre-test, implemented the instructional package, administered the posttest, and distributed the satisfaction questionnaire to the students. The data was analyzed for percentage, mean, standard deviation, and t-test. The results showed that; The efficiency of instructional package on critical thinking and figure of speech skills by using Thai popular songs, in overall, was shown at 84.05/84.75 which was higher than the 80/80 standard criteria. The learning achievement of students in the class implemented the instructional package on critical thinking and figure of speech skills by using Thai popular songs revealed the pre-test and posttest mean scores at 30.74% and 83.37% in which the posttest mean was higher than that of the pre-test at the significance level of .01. The students, in overall, showed their satisfaction at the highest level towards the use of instructional package on critical thinking and figure of speech skills by using Thai popular songs.